GOD IN ALICE WALKER'S THE COLOR PURPLE; A PARADOX OF THE DIVINE - Muna, Nailil (EduLite: Journal of English Education, Literature and Culture, 2016)
Over time, as secularization took root in Black churches during the CivilRights era, the prevalent framework in understanding African Americanspirituality discourse has shifted from theology to sociology. This paper tries to discern this major shift from the black literature perspective. It aims to discuss the main charachers' paradoxical state of mind in understanding God in the novel The Color Purple. The 1982 Pulitzer Prize for fiction winner is organized around an intimate conversation between two female characters, Celie and Shug Avery, whose understanding of God were challanged by complexity of sexism and racism in the black family. A sociological approach is adopted to understand the characters' dynamic concept of God. Discussion in this paper suggested that Alice Walker's naturalist theology is embodied in Celie and Shug Avery’s conceptualizationof God in the novel.Keywords: Black Theology, The Color Purple, God in Black Literature.